Trends in CT use in an emergency department in Western Australia: 2015–2022 - Fouziah Almouqati; Thi Ninh Ha; Sharmani Barnard; Ashu Gupta; Elizabeth Thomas; Tracey Bhar; Colleen Taylor; Delia Hendrie (Insights into Imaging)
Abstract Objectives We examined trends in CT use within the emergency department (ED) and their association with trends in subsequent hospital admission. Methods This retrospective study analyzed administrative data on episodes of adults aged 18+ years who presented to the ED of a tertiary hospital in Western Australia (WA) from March 2015 to December 2022. Adjusted annual rates of CT use and hospital admission, stratified by CT status, were estimated using multivariable regression models. Results Between 2015 and 2022, while the number of ED episodes increased by 8%, the number of CT scans rose by 90%. The crude rate of scans per 1000 ED episodes rose from 111 [95% CI: 108, 113] to 195 [95% CI: 192, 199]. After adjusting for variations in patients’ characteristics, the rate increased from 118 [95% CI: 115, 121] to 173 [95% CI: 169, 176]. Admission rates were consistently higher for patients with CT but declined over time in both groups: from 47.6% [95% CI: 46.46, 48.75] to 42.01% [95% CI: 41.12, 42.9] for those with CT, and from 27.25% [95% CI: 26.86, 27.64] to 23.83% [95% CI: 23.47, 24.2] for those without. Compared to those without CT, the admission rate in those who underwent CT decreased by 2.17% [95% CI: 3.68, 0.66] over the period. Conclusions CT use in the ED has continued to increase since 2015, coinciding with a greater decrease in admissions among patients who underwent CT. The appropriateness of this increase remains undetermined, warranting further investigation. Critical relevance statement Given the ongoing efforts to optimize CT scan use, this study evaluates its current utilization in the emergency department and its usefulness in patient management, particularly in hospital admission. Key Points Examining CT use and usefulness is vital given ongoing optimization efforts. CT rates rose significantly, with a clear upward shift from 2020. This coincided with a greater drop in admission for CT patients than non-CT. Graphical Abstract